Khandan-i-Ijtihad: Genealogy, history, and authority in a household of ‘ulama in modern South Asia - Jones, J (Cambridge University Press, 2019)
Revisiting the debate on how Islam's ‘learned men’ (‘ulama) have sustained their religious authority through changing historical circumstances, this article offers a longue durée account of the so-called ‘Khandan-i-Ijtihad’: a family of renowned scholars and jurists who have held scholarly and popular precedence within South Asia's Shi‘i clerical networks for some 250 years. Instead of analysing the ‘ulama as a corporate group or a class of religious professionals, this article examines the ‘ulama as members of households (khandan, khanwadah) and emphasizes the important role of family lineage and inherited social influence as conduits of clerical leadership. Tracing both the genealogical succession and the vocational enterprises of this family over several generations, the article proposes a framework for understanding an individual scholar's relationship with the collective household, arguing that a cleric's own reputation (hasab-va-nasab) rests on a mingling of ancestral pedigree and personal achievement, with the stature of individual and household perpetually affirming and reinforcing each other in the making of Islamic clerical authority. Furthermore, the article establishes the importance of the ‘ulama-biography (tazkirah) as itself a mechanism for actively sustaining the relevance of contemporary ‘ulama, by perpetually memorializing their ancestors.